Case report: Novel compound heterozygous IL1RN mutations as the likely cause of a lethal form of deficiency of interleukin-1 receptor antagonist - Urbaneja, Elena; Bonet, Nuria; Solis-Moruno, Manuel; Mensa-Vilaro, Anna; de Landazuri, Iñaki Ortiz; Tormo, Marc; Lara, Rocio; Plaza, Susana; Fabregat, Virginia; Yagüe, Jordi; Casals, Ferran; Arostegui, Juan I. (Frontiers in Immunology, 2024)
Undiagnosed monogenic diseases represent a challenging group of human conditions highly suspicious to have a genetic origin, but with not conclusive evidences about it. We identified two brothers born prematurely from a non-consanguineous healthy couple, with a neonatal-onset, chronic disease characterized by severe skin and bone inflammatory manifestations, and a fatal outcome in infancy. We conducted DNA and mRNA analyses in patients' healthy relatives to identify the genetic cause of the patients' disease. DNA analyses were performed by both Sanger and next-generation sequencing, which identified two novel heterozygous IL1RN variants: the intronic c.318+2T>G variant in the father, and a »2600bp intragenic deletion in the mother. IL1RN mRNA production was markedly decreased in both progenitors when compared with healthy subjects. mRNA sequencing performed in each parent identified two novel, truncated IL1RN transcripts. Additional experiments revealed a perfect intrafamilial phenotype-genotype segregation following an autosomal recessive inheritance pattern. The evidences here shown supported for the presence of two novel lossof-function (LoF) IL1RN pathogenic variants in the analyzed family. Biallelic LoF variants at IL1RN gene cause the deficiency of interleukin-1 receptor antagonist (DIRA), a monogenic autoinflammatory disease with marked similarities with the patients here described. Despite the non-availability of the patients' samples represents the main limitation of this study, collected evidences strongly suggest that patients here described suffered from a lethal form of DIRA likely due to a compound heterozygous genotype at IL1RN, thus providing a reliable genetic diagnosis based on the integration of old medical information with currently obtained genetic data.